Editorial, Vol. 6, No. 2 - Alessandro De Gloria (Serious Games Society, 2019)
This edition of the International Journal of Serious Games is mostly dedicated to a special issue on "Gamification of Industrial Systems", guest edited by Samir Garbaya and Theo Lim. The special issue aims at investigating new emerging needs for gamification in industry.  The issue features six articles, that address important challenging issues through conducting pilot studies and developing gamified industrial applications. The issue is completed by a regular paper  by Batista et Al.